Digital Dependency and Learning: a Correlational Study of AI Dependency, Academic Self-Efficacy, Motivation, and Procrastination among Students - Muhammad Rafli Iltizamulloh; Salwa Naira Aluina Jasmine (Psychology Journal of Mental Health, 2025)
The use of Artificial Intelligence (AI) has rapidly increased among university students, with many utilizing AI chatbots such as ChatGPT, Gemini, and DeepSeek to support their academic activities. This phenomenon raises concerns about potential dependency on AI, which may influence psychological aspects of learning, such as self-efficacy, motivation, and procrastination. This study aims to analyze the relationship between AI chatbot dependency and academic self-efficacy, academic motivation, and academic procrastination among students. A quantitative approach was employed using a survey method involving 102 students aged 18–23 years. Data were analyzed using Pearson’s correlation with the assistance of SPSS version 29. The results showed that AI chatbot dependency had a significant positive correlation with academic motivation (r = .282; p < .05), but no significant correlation with self-efficacy (r = .152; p > .05) or procrastination (r = .168; p > .05). These findings indicate that the use of AI chatbots may enhance students’ learning motivation but does not necessarily affect their self-belief or tendency to delay academic tasks. Practically, this study provides insights for developing guidelines on the healthy and balanced use of AI chatbots in academic settings.